The Comparison of Guided Inquiry Learning with Problem Based Learning toward Science Process Skills of Students’ Enviromental Pollution Material in Junior High School - Mahdiyah Hermanto; Noor Hujjatusnaini; Ridha Nirmalasari (Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
This study aims (1) to determine whether the guided inquiry learning model has an effect on the students' science process skills, (2) to find out whether the PBL learning model affects the students' science process skills, (3) to find out the differences in the students' science process skills. VII SMPN 5 Dusun Selatan which uses the guided inquiry learning model and the PBL learning model. The method in this research is comparative quantitative. The research design used was the Nondomized Control Group Pretest-Posttest Design. The instrument used was a test in the form of multiple choice questions totaling 25 questions and an observation sheet for students' science process skills. The research sample was students of class VII A and class VII B at SMPN 5 Dusun Selatan. The data collection technique was carried out using the observation method of students' science process skills and learning outcomes tests. The data were analyzed descriptively. The results of this study show that (1) the value of the science process skills of students using the guided inquiry learning model has an average value of 92%, (2) the value of the science process skills of students using the PBL learning model has an average value of 96 %, (3) the difference in the science process skills of students who are taught using the guided inquiry learning model and the PBL learning model, it can be seen from the results of the average value obtained that there are differences, where the PBL learning model has a higher average value than the learning model. guided inquiry. The learning outcomes of the guided inquiry class had an average score of 39 on the pretest and 68 on the posttest. Meanwhile, the average value of the pretest in the PBL class was 40.4 and the posttest score was 69.3. These results indicate that the guided inquiry learning model and the PBL learning model can improve students' learning outcomes and science process skills.